Procurement of Foreign-Funded Projects Through Executive Agreements as Potential Sources of Corruption in Government: Going Beyond the Case of Abaya vs. Ebdane - Cadapan-Antonio, Myrish T.; de Asis Ruperto, Ramon Antonio (Silliman Journal, 2022)
The enactment of the first comprehensive law on public procurement in the Philippines, Republic Act No. 9184, was regarded as a significant feat to the fight against corruption. Only five years after its enactment and while the Implementing Rules on foreign-assisted projects is still being formulated, a public procurement scandal erupted involving key government officials including the President herself and the First Gentleman. This infamous NBN-ZTE scandal was exposed shortly after the Philippine Supreme Court decided the case entitled Abaya vs. Ebdane which exempted procurement contracts made through executive agreement from the realm of RA 9184. During the Senate investigation of the controversy, reference to Abaya vs. Ebdane was numerously made. This jurisprudence and the said usage in this scandal creates legal and moral issues that the authors wish to dissect in the hope of awakening significant policy initiatives related thereto.